2013
DOI: 10.1309/ajcpe5i3keltbxej
|View full text |Cite
|
Sign up to set email alerts
|

Small-Dense LDL Cholesterol/Large-Buoyant LDL Cholesterol Ratio as an Excellent Marker for Indicating Lipodystrophy in HIV-Infected Patients

Abstract: The sdLDL-C/lbLDL-C ratio is an excellent marker for indicating lipodystrophy in HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…A recent study by Lee et al [ 20 ] determined that the sdLDL/lbLDL ratio increases during the development of impaired fasting glucose and is strongly associated with insulin resistance, suggesting atherogenic dyslipidemia from a pre-diabetic stage. A high sdLDL/lbLDL ratio has also been shown to be associated with lipid metabolic disturbance in patients with metabolic syndrome and human immunodeficiency virus (HIV)-associated lipodystrophy [ 21 , 22 ]. Although a different analytic methodology was used to measure the number of lipoprotein particle in this study, the sdLDL-P/lbLDL-P ratio in pregnant women was positively correlated with fasting glucose after adjusting for age and BMI, two factors known to affect lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Lee et al [ 20 ] determined that the sdLDL/lbLDL ratio increases during the development of impaired fasting glucose and is strongly associated with insulin resistance, suggesting atherogenic dyslipidemia from a pre-diabetic stage. A high sdLDL/lbLDL ratio has also been shown to be associated with lipid metabolic disturbance in patients with metabolic syndrome and human immunodeficiency virus (HIV)-associated lipodystrophy [ 21 , 22 ]. Although a different analytic methodology was used to measure the number of lipoprotein particle in this study, the sdLDL-P/lbLDL-P ratio in pregnant women was positively correlated with fasting glucose after adjusting for age and BMI, two factors known to affect lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Study population: This is a retrospective case-control study conducted on 85 HIV-infected patients who visited the Infectious Diseases Clinic of Ramathibodi Hospital, Mahidol University, in Bangkok, Thailand between March 2006 and February 2007; these patients were from a previous study (7,(19)(20)(21). The inclusion criteria were as follows: the HIV-infected patients should be adults (15 years old) who were maintained on antiretroviral regimens.…”
Section: Methodsmentioning
confidence: 99%
“…In each biannual visit, serum cholesterol and triglyceride measurements are obtained from our study participants, and were used to define our atherogenic and atheroprotective groups. Other measurements, such as lipoprotein particle size and number, and HDL efflux capacity, have been shown to be stronger predictors of cardiovascular disease risk [ 58 , 59 ], and would have been collected on subsequent visits had our initial study shown a role for CNV in this pathway. Our samples were also collected prior to the widespread use of the 2013 ACC/AHA guideline, and we therefore use the older NCEP ATP III panel, but our data are based on a sufficiently large sample size to overcome this issue.…”
Section: Discussionmentioning
confidence: 99%